2018
DOI: 10.1051/0004-6361/201834067
|View full text |Cite
|
Sign up to set email alerts
|

Line shapes of the magnesium resonance lines in cool DZ white dwarf atmospheres

Abstract: Context. Line shapes of the magnesium resonance lines in white dwarf spectra are determined by the properties of magnesium atoms and the structure of the white dwarf atmosphere. Through their blanketing effect, these lines have a dominant influence on the model structure and thus on the determination from the spectra of other physical parameters that describe the stellar atmosphere and elemental abundances. Aims. In continuation of previous work on Mg + He lines in the UV, we present theoretical profiles of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
4
8
0
Order By: Relevance
“…Such an abundance may be typical of comets, but the upper limits on H, O, and Na suggest that the accreted material is not rich in volatiles, and that the decreasing phase is the more likely cause of the C enhancement. Similar conclusions could be reached using the abundances presented in a recent analysis of this star (Allard et al 2018), where measurements in common with this study agree within the uncertainties.…”
Section: Individual Objectssupporting
confidence: 91%
“…Such an abundance may be typical of comets, but the upper limits on H, O, and Na suggest that the accreted material is not rich in volatiles, and that the decreasing phase is the more likely cause of the C enhancement. Similar conclusions could be reached using the abundances presented in a recent analysis of this star (Allard et al 2018), where measurements in common with this study agree within the uncertainties.…”
Section: Individual Objectssupporting
confidence: 91%
“…In our code, we use profiles computed with the unified line broadening theory (Allard & Kielkopf 1982;Allard et al 1999) and accurate ab initio potentials to model the Mg-He interaction. This approach has repeatedly been shown to be in good agreement with laboratory measurements (Kielkopf & Allard 1998;Allard & Kielkopf 2009;Allard et al 2012Allard et al , 2016b, brown dwarf spectra (Allard et al 2003) and white dwarf spectra (Allard et al 2016a(Allard et al , 2018Blouin et al 2019a,b) under conditions similar to those found at the photospheres of the objects in our sample. The choice of Hollands et al (2017) to use the Walkup et al (1984) interpolation algorithm instead of the more accurate unified theory of Allard et al (1999) largely stems from their finding that unified Mg b triplet profiles lead to an absorption maximum that is too far to the blue of the low-density maximum to fit the spectra of cool DZ white dwarfs.…”
Section: Metal Abundancessupporting
confidence: 90%
“…As a consequence, the photosphere is located deeper into the white dwarf, where the density is higher (e.g., Bergeron et al 1995). Under such conditions, the constitutive physics of atmosphere models becomes increasingly challenging as many-body interactions between particles affect the chemical equilibrium (Kowalski et al 2007;Blouin et al 2018a), the equation of state (Saumon et al 1995), the continuum opacities (Iglesias et al 2002;Rohrmann 2018) and the spectral line profiles (Koester et al 2011;Allard et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that manybody collisions must be included in our calculation of the Ca I resonance line pressure broadening and this is why we rely on the autocorrelation formalism of Allard et al (1999). This approach has already proved successful for the modeling of spectral lines in cool DZ white dwarfs (e.g., Allard et al 2016Allard et al , 2018. Another proof of the accuracy of the Allard et al (1999) formalism has been provided by the study of He doped with alkali atoms, which has recently been a subject of active study (e.g., Hernando et al 2010;Mateo et al 2011).…”
Section: High Densitiesmentioning
confidence: 99%